Prediction of Psychological Well-being and Social Adjustment Based on Parent-Child Relationship Pattern in Adolescents with Divorced Parents in Hamadan - Rabbani, Zeinab (Iranian Journal of Neurodevelopmental Disorders, 2023)
Introduction and purpose: The purpose of this research is to predict psychological well-being and social compatibility based on the pattern of parent-child relationship in teenagers with divorced parents in Hamadan city. Method: The research design is descriptive of the correlation type. For this purpose, by referring to the welfare centers of Hamadan city, 260 teenagers from divorced families were selected by two-stage random sampling method and psychological well-being questionnaires (Reif, 2002), students’ social adjustment questionnaire (Sinha and Singh, 1993) and They answered the parent-child relationship model questionnaire (Bagheri, 2011). Research data were analyzed using Pearson’s correlation test and multiple regression analysis method. Findings: The results showed that among the components of the parent-child relationship pattern, the components of formality, indecisiveness, pampering and entanglement negatively predicted the psychological well-being of adolescents. Also, among the components of the parent-child relationship model, only the control component negatively predicted the social adjustment of adolescents. Conclusion: Therefore, it can be concluded that in divorced families, the way the guardian parent communicates affects the psychological well-being and adaptation of adolescents. In this way, the more permissive, irregular, or cold and formal the parents’ parenting style is, the psychological well-being of adolescents decreases. Also, extreme control and supervision reduces their social adjustment.